KEBERAGAMAN MASYARAKAT DAN TOLERANSI BERAGAMA DALAM SEJARAH KERAJAAN SRIWIJAYA (SUATU ANALISIS HISTORIS DALAM BIDANG SOSIAL, BUDAYA, EKONOMI DAN AGAMA) - Sholeh, Kabib (Siddhayatra, 2018)
The kingdom of Sriwijaya was known as the greatest protector and follower of Buddhism in the archipelago of his time. The diversity of society, race and religion make Sriwijaya truly able to maintain peace, diversity and tolerance among religious people.. The purpose of this study is to analyze the diversity of society in the kingdom of Sriwijaya in various aspects of life, tolerance among religious communities between Buddhism, Islam and Hinduism, and the factors emergence of life tolerance in the kingdom of Srivijaya. The method used is historical method. The steps in historical methods include heuristics (data collection / source), verification (selection or source criticism), interpretation (historical interpretation) and the last is historiography (historical writing). This research explains the diversity of society in the Sriwijaya kingdom from indigenous peoples, Arabs, Indians and Chinese, and the foreign community is in the kingdom of Sriwijaya due to economic factors and they enter by trade. The diversity of the people in the kingdom of Sriwijaya is highly protected by the king of Sriwijaya kingdom so there is no emphasis, murder, threats from the king of Sriwijaya kingdom unless they do the rebellion will be burned. The king of the kingdom of Sriwijaya felt happy and respected the diversity of his people. The king of the kingdom of Sriwijaya is open to strangers, loving peace based on the unreliability of leadership in accordance with his Buddhist teachings. Such conditions have an impact on the policy of the king of Sriwijaya kingdom in addressing a difference in running beliefs and religions such as Buddhism, Islam, Hinduism and local beliefs. Sriwijaya highly upholds religious tolerance as depicted on the Hindu temple site Bumiayu temple, the arrival andsettlement of Muslim traders in the kingdom of Sriwijaya, so that the kingdom of Sriwijaya sent a letter to the Umayyads to request the sending of a mubaleq as king's adviser. All these evidences depict the king of the kingdom of Sriwijaya very tolerant of other religions.